A palaeoenvironmental record of the Southern Hemisphere last glacial maximum from the Mount Cass loess section, North Canterbury, Aotearoa/New Zealand. (July 2021) - Almond, Peter C.; Gulyás, Sándor; Sümegi, Pál; Sümegi, Balázs P.; Covey-Crump, Stephen; Jones, Merren; Shaw, Joseph; Parker, Andrew
Abstract: Calcareous loess in North Canterbury, eastern South Island, New Zealand (NZ), preserves subfossil bird bone, terrestrial gastropods, and eggshell, whose abundances and radiocarbon ages allowed us to reconstruct aspects of palaeoenvironment at high resolution through 25 to 21 cal ka BP. This interval includes millennial-scale climatic variability during the extended last glacial maximum (30–18 ka) of Australasia. Our loess palaeoclimatic record shows good correspondence with stadial and interstadial climate events of the NZ Climate Event Stratigraphy, which were defined from a pollen record on the western side of South Island. An interstade from 25.4 to 24 cal ka BP was warm but also relatively humid on eastern South Island, and loess grain size may indicate reduced vigour of the Southern Hemisphere westerly winds. The subsequent stade (24–22.6 cal ka BP) was drier, colder, and probably windier. The next interstade remained relatively dry on eastern South Island, and westerly winds remained vigorous. The 25.4–24 ka interstade is synchronous with Heinrich stade 2, which may have driven a southward migration of the subtropical front, leading to warming and wetting of northern and central South Island and retreat of Southern Alps glaciers at ca. 26.5 ka.